A framework for classifying sustainable logistics innovations - Maria Björklund; Helena Forslund (Logistics Research, 2018)
Researchers and practitioners alike need support in the challenges to develop sustainable logistics, and one cannot afford to have a limited view of what constitutes sustainable logistics innovation (SLI). In order to inspire researchers and practitioners to expand their mindset when addressing sustainable logistics, the purpose of this paper is to develop a framework for classifying sustainable logistics innovations, and by classifying some SLIs evaluating the applicability of the framework. The study is based on a literature review within logistics innovation, sustainable innovation, and sustainable logistics innovation, resulting in a framework. It contains three areas: softness, extent of change and scope, which in turn contain nine dimensions. Interviews in three retailers acting in Sweden were conducted. SLIs were illustrated and classified in the framework. By moving outside how research so far has studied SLIs, examples of SLIs in logistics activities other than transport were identified, in forms aside from technological solutions, and in industries outside of logistics service providers. It was found that it was possible to classify SLIs in all dimensions, with some difficulties in extent of change in output, which also shows the applicability of the framework. Using the framework, SLIs can be understood in a more concrete and applicable way, which can inspire practitioners to develop and expand their efforts towards sustainable logistics. Therefore the study has implications for research, practice and society. Several suggestions for future research are presented.
Keywords: 650; innovation; corporate social sustainability; sustainable logistics; retailers; framework